Diversity and morphology of the species of Pseudo-nitzschia (Bacillariophyta) of the national park Sistema Arrecifal Veracruzano, SW Gulf of Mexico - Parsons, Michael L.; Okolodkov, Yuri B.; Aké-Castillo, José A. (Instituto de Ecología, A.C., 2022)
In order to evaluate the risk for marine ecosystem and human health, the diversity and morphology of diatoms of the genus Pseudo-nitzschia were studied. Weekly sampling was performed at seven geo-referenced sites in the National Park Sistema Arrecifal Veracruzano, SW Gulf of Mexico, during the annual cycle from May 2005 to May 2006. Samples were taken in the 30-cm surface layer of the water column with a phytoplankton net of 20-µm mesh size. With the use of light, transmission and scanning electron microscopy, seven Pseudo-nitzschia species were identified: non-toxic P. cf. subcurvata (examined only by light microscopy) and P. brasiliana, and potentially toxic, causative agents of amnesic shellfish poisoning (ASP) due to domoic acid: P. calliantha, P. cuspidata, P. delicatissima, P. pseudodelicatissima and P. pungens. It is concluded that there is a potential risk of ASP in the study area. P. brasiliana and P. calliantha are new records for the SW Gulf of Mexico. Comparisons with studies conducted in the northern Gulf of Mexico indicate that the diversity of Pseudo-nitzschia in the Gulf of Mexico may be greater than currently documented and that some species (e.g., P. multiseries) may have biogeographic limitations (e.g., temperatures below 27 oC).